Her Majesty's Texans : two English immigrants in Reconstruction Texas - Robertson, Robert J. (Centennial series of the Association of Former Students, Texas A & M University, 1998)
During Queen Victoria's reign, many working-class immigrants came to America. Because of their shared language, Anglo ethnicity, and familiarity with English-based customs, these immigrants rapidly blended into American life. John W. Leonard and J.W.L. "Will" Johnson were two such Englishmen; they came to Beaumont, Texas, in 1869, assimilated quickly, and became "invisible immigrants." Living in Beaumont for almost fifteen years, Johnson and Leonard carved out careers as teachers, lawyers, and newspapermen. Johnson operated a school, edited the Neches Valley News, and helped organize the East Texas River and Harbor Improvement Association. Leonard established the Beaumont Enterprise and founded the town's first Episcopal congregation. Both became heavily involved in Reconstruction politics, adopting the racial and political attitudes of conservative white Texans. As fledgling Democrats, they worked to rebuild the party, defeat the Republicans, and thereby "redeem" the state. In Her Majesty's Texans, Robert J. Robertson presents a fascinating story, recounting not only Johnson's and Leonard's business and political careers, but also their personal lives. -- Provided by publisher